2002
DOI: 10.1007/s004060200014
|View full text |Cite
|
Sign up to set email alerts
|

Neurofunctional correlates of posttraumatic stress disorder: a PET symptom provocation study

Abstract: Patients with combat-related posttraumatic stress disorder (PTSD) show altered cognitive and affective processing and symptomatic responding following exposure to trauma reminders. Previous symptom provocation studies using brain imaging have involved Vietnam veterans. In this study neural correlates were investigated in patients with PTSD resulting from trauma in more recent war zones. (15)Oxygen water and positron emission tomography were used to measure regional cerebral blood flow (rCBF) in patients with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(123 citation statements)
references
References 45 publications
6
114
0
3
Order By: Relevance
“…amygdala hyperresponsivity with apparent exaggerated responses in PTSd has been reported (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). cui et al additionally found that behavioral changes in response to SPS may be attributed to the amygdala (20).…”
Section: Introductionmentioning
confidence: 84%
“…amygdala hyperresponsivity with apparent exaggerated responses in PTSd has been reported (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). cui et al additionally found that behavioral changes in response to SPS may be attributed to the amygdala (20).…”
Section: Introductionmentioning
confidence: 84%
“…In this way, neural activity can be studied when subjects are exposed to stimuli reminiscent of their traumatic past. Studies of Vietnam combat veterans have used combat sounds [Bremner et al, 1999b;Liberzon et al, 1999;Pissiota et al, 2002;Zubieta et al, 1999] and combat slides [Bremner et al, 1999b;Hendler et al, 2003] to induce trauma-related stress by symptom provocation. Other studies that include victims of sexual assault or abuse have used personal traumatic scripts [Britton et al, 2005;Gilboa et al, 2004;Lanius et al, 2001Lanius et al, , 2002Lanius et al, , 2005Liberzon, 2003;Rauch et al, 1996;Shin et al, 2004a] to elicit an emotional response.…”
Section: Functional Neuroimaging Paradigmsmentioning
confidence: 99%
“…The latter technique induces traumatic imageries and thus mimics flashbacks of the aversive events (as evidenced by both subjective ratings and psychophysiological parameters) by reading accounts of their individual traumatic experiences to patients during functional imaging. 15 Increased activation of the right amygdala was found across provocation techniques and imaging modalities, [15][16][17] while medial prefrontal areas were consistently reported to be less active in PTSD patients than controls when traumatic events had to be recalled. 18,19 In regions of the medial temporal cortex commonly associated with memory retrieval and visual association areas involved in mental imagery both higher and lower activation have been reported for PTSD patients, possibly reflecting the heterogeneity of patient samples across studies.…”
mentioning
confidence: 99%